Effects of Nitrous Oxide on Chloral Hydrate Sedation of Young Children - Houpt, Milton I. (1986)
This study was performed to test the hypothesis that nitrous oxide augments the effects of chloral hydrate sedation of young children. Twenty children with a mean age of 32 months were sedated on two occasions with two different treatment regimens. All subjects received a standard dose of 50 mg/kg of chloral hydrate with or without nitrous oxide during each of two treatment visits. During one visit, the subjects received 50% nitrous oxide and 50% oxygen for a period of 20 minutes followed by 100% oxygen and, during the other visit, the reverse concentrations were used. All subjects were restrained in a Papoose Board(*) with an auxiliary head restraint. Successful sedation, as evident by lack of crying or movement which interrupted treatment, occurred in 84% of administrations. During the first twenty minutes, subjects receiving nitrous oxide moved and cried significantly less than when they were treated without nitrous oxide. During the remainder of the appointment, there was no difference in behavior between the two treatment regimens. Vital signs remained essentially unchanged throughout all treatment with the exception of transitory elevation of the pulse and respiratory rates, which usually occurred when the mouth prop was inserted and local anesthesia was administered. It is concluded that nitrous oxide augments the effect of chloral hydrate sedation of young children, but does not do so uniformly for all children receiving sedation.